The Role of Traditional and Alternative Health Systems In Providing Health Care Options: Evidence from Kerala - Deepa Sankar
In the context of growing interest and demand for traditional and alternative systems of medicines, this paper tries to understand the nature of the demand for these systems in the context of Kerala, South India where the traditional and alternative systems of medicines are preserved are institutionalised by the government and provided in large number by the private sector. Based on the utilisation of health services data collected through a primary survey in a district in the state, the analysis shows that the traditional and alternative systems of medicines are demanded and used according to the specificity of the need of the hour. The analysis showed that people are not choosing the traditional or homeopathic systems as alternatives to modern medicines or as the last resort; rather, they have specific purpose for choosing them as patients distinguish certain systems of medicines as better suited for the treatment of specific diseases. It showed that systems like Ayurveda and homeopathy should be seen as 'complementary' rather than as 'alternative' to the modern medicines, indicating the need for integrating the different systems of medicines or collaboration and partnerships between systems of medicines for the better health care provision in the society.